Analisis Pengendalian Kualitas Untuk Mengurangi Kecacatan Pada Produksi Kain Tenun Dengan Metode Seven Tools Di PT Kain Ratu Utama - Syaina Putri Fajria Agustin; Gunawan Mohammad; Gun Sudiryanto; Boedi Lofian (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the quality control of woven fabric production at PT Kain Ratu Utama using the Seven Tools method. The problem studied is the high level of defects in woven fabric products produced, such as netting (fabric not woven), loose weaving, tangled threads, and patterns that do not match the pattern. The resolution of this problem is important because the high level of defects has a negative impact on product quality and the company's operational efficiency, which in turn affects the company's competitiveness in the market. The research method used is descriptive quantitative with data collection through direct observation and interviews. The research stages include defect data collection, analysis using seven quality control tools (Check Sheet, Control Chart, Histogram, Pareto Diagram, Scatter Diagram, Fishbone Diagram, and Stratification), and identification of the main causes of defects. The results showed that the highest defect was the netting category with 151 sheets (27%). The main causes of defects come from machine malfunctions and human factors. By applying the Seven Tools method, the company can effectively identify and reduce the level of defects, thereby improving product quality and production process efficiency.